Degeneration of the corticofugal tract from the secondary motor area in a Parkinson's disease patient with limb-kinetic apraxia: A case report. Issue 50 (December 2017) - Lee, Han Do; Chang, Min Cheol
Abstract: Rationale: In this case report, we describe a Parkinson's disease (PD) patient with limb-kinetic apraxia (LKA) in whom degeneration of the corticofugal tract (CFT) from the supplementary motor area (SMA) was observed in diffusion tensor tractography (DTT). Patient concerns: A 63-year-old woman presented with a loss of dexterity in both upper extremities, which indicated LKA, and typical PD-related symptoms, including a gait disturbance with a short step, resting tremor in both upper extremities, and rigidity, and these symptoms had been present for 2 years. The 18 F-florinated- N -3-fluoropropyl-2-β-carboxymethoxy-3-β-(4-lodophenyl) nortropane positron emission tomography scanning findings were consistent with PD. Based on the clinical symptoms and imaging findings, we diagnosed the patient with PD. In a coin-rotation test that was used to evaluate the severity of the LKA, the patient's results significantly decreased compared to the results of the normal controls. Diagnoses: The DTT showed that the CFTs from the SMAs in both hemispheres were partially torn and thinned. The fractional anisotropy values and CFT volumes in both SMAs were >2 standard deviations lower than those of the normal controls. Interventions: The patient was treated with an initial dose of 150/37.5 mg/day of levodopa/benserazide, and the dose was gradually increased to 400/100 mg/day. Outcomes: After treatment, although the bradykinesia, rigidity, and resting tremor of the patient significantly decreased, the dexterity of the patient's hands did not improve. Lessons: These observations indicated degeneration of the CFTs from the SMAs in both hemispheres in the patient. This degeneration might have, at least in part, contributed to the patient's LKA. The results of this study suggest that CFT degeneration could be one of the pathological mechanisms underlying LKA in patients with PD.